Evaluasi Proses Persetujuan Kredit Perbankan Korporasi Dengan metode Lean Six Sigma (Studi Kasus Pada PT Bank ABC, Tbk.) - , DEVI PRAYHAJENG FADREANDINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesian banking industry has shown a very tight competition among banks, both in gathering funds and giving loan. Time of loan approval has become very important aside from competitive interest rate. A fast and simple credit approval process proven to be one of the main reason why a prospective customer choose a bank instead of others. The research will focus on the evaluation of credit approval process, especially in PT. Bank ABC corporate banking segment. Lean Six Sigma will be used as method of credit process evaluation at PT. ABC Bank. This method was chosen due to emphasize to the needs of customers. With Lean method, PT. Bank ABC can speed up the process and eliminate processes that do not provide added value. While Six Sigma method process improvements can be made with more structured and measurable. With process improvement, PT. Bank ABC is expected to achieve, maintain and maximize their business success.